Public perception of medical detection dogs and other COVID-19 testing strategies - Zacharias, Karolina; Meller, Sebastian; ten Hagen, Nele A.; Volk, Holger A.; Twele, Friederike (Frontiers in Public Health, 2025)
The COVID-19 pandemic led to social restrictions, severely impacting many sectors, including the cultural and gastronomic sectors. To restore normality, various testing approaches were proposed, but public opinion and acceptance of these tests in Germany had not been investigated. Proposed solutions included antigen rapid diagnostic tests (Ag-RDTs), polymerase chain reaction (PCR) tests, and medical detection dogs. The aim of the current study was to assess public perceptions regarding the use of canines for SARS-CoV-2 detection. A feasibility study on SARS-CoV-2 detection using trained detection dogs was conducted among 2,802 concertgoers across four events. Participants aged 18 years and older, provided informed consent, shared their medical history, and completed a survey on various testing methods. They then underwent PCR testing, Ag-RDTs, and canine testing. After the concerts, 1,315 participants completed a follow-up survey about their experiences with the different testing systems. Before the concerts, 70% of respondents preferred using dogs for testing, with 32% favoring direct sniffing and 39% preferring sweat sample testing. After the concert, 72% still preferred canine testing, with 40% voting for direct sniffing and 32% for indirect sweat sample testing. Twenty-one percent preferred PCR testing before the concerts and 23% afterwards. Respondents also recommended deploying medical detection dogs at large events, such as concerts, and at transportation hubs. However, opinions were divided on their use for SARS-CoV-2 screening in schools. These results underscore the importance of context-specific testing strategies and standardized guidelines for canine detection. While many participants preferred direct sniffing, the sweat sample method emerged as a more practical and privacy-conscious alternative. The study provides valuable insights into public acceptance of various testing methods and emphasizes the potential of canine testing at large events. Clear guidelines and proper training of detection dogs will be crucial for future pandemic preparedness.